DNA methylation-based classification and identification of bladder cancer prognosis-associated subgroups - Tian, Zijian (Cancer Cell Int, 2020)
BACKGROUND: Bladder cancer (BCA) is the most common urinary tumor, but its pathogenesis is unclear, and the associated treatment strategy has rarely been updated. In recent years, a deeper understanding of tumor epigenetics has been gained, providing new opportunities for cancer detection and treatment. METHODS: We identified prognostic methylation sites based on DNA methylation profiles of BCA in the TCGA database and constructed a specific prognostic subgroup. RESULTS: Based on the consistent clustering of 402 CpGs, we identified seven subgroups that had a significant association with survival. The difference in DNA methylation levels was related to T stage, N stage, M stage, grade, sex, age, stage and prognosis. Finally, the prediction model was constructed using a Cox regression model and verified using the test dataset; the prognosis was consistent with that of the training set. CONCLUSIONS: The classification based on DNA methylation is closely related to the clinicopathological characteristics of BCA and determines the prognostic value of each epigenetic subtype. Therefore, our findings provide a basis for the development of DNA methylation subtype-specific therapeutic strategies for human bladder cancer.